Unidade prisional de Parintins/Amazonas: análise crítica sobre os dilemas da ressocialização dos apenados no cenário amazônico - Souza, Denilce Santos de (Brasil, 2025)
This work is a research of critical analysis, regarding the dilemmas of the resocialization of convicts in the Amazonian scenario, having as locus the Prison Unit of Parintins Amazonas, analyzing the problems that conflict in the resocialization of prisoners of the Prison Unit of Parintins. Place where the prison population of the municipality is centered, starting from the objective of analyzing the Parintins Prison Unit, with emphasis on the challenges of the rehabilitation of people deprived of liberty and the performance of Social Service. The research is exploratory, with a bibliographic approach, based on the method of study of dialectical historical materialism, in order to deepen the intrinsic dimensions of the reality posed. The methodological path was carried out through an institutional visit to the Parintins Prison Unit, through a non-participant observation, in order to analyze the structural conditions of the place. As a result, it is highlighted that, according to the critical analysis of the dilemmas, the violation of the rights of the inmates of the Parintins prison system is evident, which contributes to the process of marginalization of the prisoners, with repercussions for their criminal recidivism.